2013
DOI: 10.1093/brain/awt211
|View full text |Cite
|
Sign up to set email alerts
|

Shape shifting pain: chronification of back pain shifts brain representation from nociceptive to emotional circuits

Abstract: Chronic pain conditions are associated with abnormalities in brain structure and function. Moreover, some studies indicate that brain activity related to the subjective perception of chronic pain may be distinct from activity for acute pain. However, the latter are based on observations from cross-sectional studies. How brain activity reorganizes with transition from acute to chronic pain has remained unexplored. Here we study this transition by examining brain activity for rating fluctuations of back pain mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
562
9
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 629 publications
(646 citation statements)
references
References 85 publications
39
562
9
9
Order By: Relevance
“…The dynamics of corticolimbic reverberating loops depend both on the preexisting limbic brain circuitry and on the reorganization following the inciting event, and these interactions will determine the likelihood of either recovering from or transitioning to chronic pain. chronic pain or transition to chronic pain activates the amygdala in relation to subjective perception of the chronic pain (Baliki et al 2006;Hashmi et al 2013). The mPFC's neuronal activity and morphology change in various animal models of persistent pain (Metz et al 2009;Kiritoshi and Neugebauer 2015).…”
Section: Corticolimbic Signaling and Transition To Chronic Painmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamics of corticolimbic reverberating loops depend both on the preexisting limbic brain circuitry and on the reorganization following the inciting event, and these interactions will determine the likelihood of either recovering from or transitioning to chronic pain. chronic pain or transition to chronic pain activates the amygdala in relation to subjective perception of the chronic pain (Baliki et al 2006;Hashmi et al 2013). The mPFC's neuronal activity and morphology change in various animal models of persistent pain (Metz et al 2009;Kiritoshi and Neugebauer 2015).…”
Section: Corticolimbic Signaling and Transition To Chronic Painmentioning
confidence: 99%
“…The mPFC's neuronal activity and morphology change in various animal models of persistent pain (Metz et al 2009;Kiritoshi and Neugebauer 2015). In humans, the region reflects subjective chronic pain intensity, and its functional connectivity with the NAc is predictive of transition to chronic pain (Baliki et al 2006;Baliki et al 2012;Hashmi et al 2013). Moreover, human evidence now shows that hippocampal intrinsic connectivity and hippocampal cortical connectivity are modified with transition to chronic pain (Mutso et al 2013).…”
Section: Corticolimbic Signaling and Transition To Chronic Painmentioning
confidence: 99%
“…The improved self-efficacy scores in the MBSR group suggest MBSR may diminish perceived helplessness associated with the chronic pain of IC/BPS. As opposed to acute pain, which is related to nociceptive signals at the level of tissue damage, chronic pain appears to be processed in regions of the brain associated with emotion and reward [21]. This may explain why therapies that target the bladder are incompletely effective in many patients.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to chronic pain, it has been suggested that shifting the focus from 'an infringed sensory system' to 'an emotion system' is essential for advancing mechanistic understanding (26). In addition, it is thought that pain arising from damage and inflammation is associated with mental and physical stress (27).…”
Section: Discussionmentioning
confidence: 99%